The Effect of Mobile Banking Service Effectiveness in Improving Customer Transaction Convenience - Ramadhani, Digita Desri; Kurniawan, Dedi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
The aim of this research is to investigate how customer interest in using mobile banking services is influenced by benefits, trust, and simplicity of use., especially on the experiences and difficulties faced by customers in using online banking services, with a focus on online payments, online fund transfers, online shopping and account mutation history monitoring. There are two main uses of variables to conduct research with the details of dependent variables being customer interest, while independent variables include benefits, trust, and ease of use. This study employs a quantitative methodology that makes use of the Slovin formula and primary data obtained from surveys. A total of 128 business management majors from Batam State Polytechnic's Managerial Accounting Study Program made up the study's sample. This study utilized multiple linear regression analysis, t-tests, and classical assumption tests as its primary data analytic methods. The findings revealed that consumer interest was positively influenced to a small extent by the benefit variable, significantly positively influenced by the trust variable, and significantly positively influenced by the ease of use variable.